2021
DOI: 10.1161/jaha.121.022482
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profile of Endotoxemia Reveals an Association With Thromboembolism and Stroke

Abstract: Background Translocation of lipopolysaccharide from gram‐negative bacteria into the systemic circulation results in endotoxemia. In addition to acute infections, endotoxemia is detected in cardiometabolic disorders, such as cardiovascular diseases and obesity. Methods and Results We performed a genome‐wide association study of serum lipopolysaccharide activity in 11 296 individuals from 6 different Finnish study cohorts. Endotoxemia was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Genetic polymorphisms contributing to serum lipopolysaccharide activity were associated with the risk of “ischemic stroke,” “any stroke,” “TOAST small artery occlusion,” “TOAST cardioaortic embolism,” and “intracranial aneurysm” in the Megastroke population, whereas the genetic risk score of lipopolysaccharide activity presented associations with deep vein thrombosis, pulmonary embolism, and venous thromboembolism 117 . Even a causal association of lipopolysaccharide in stroke was suggested in this study, which is the first one exploring the genetic background of endotoxemia 117 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic polymorphisms contributing to serum lipopolysaccharide activity were associated with the risk of “ischemic stroke,” “any stroke,” “TOAST small artery occlusion,” “TOAST cardioaortic embolism,” and “intracranial aneurysm” in the Megastroke population, whereas the genetic risk score of lipopolysaccharide activity presented associations with deep vein thrombosis, pulmonary embolism, and venous thromboembolism 117 . Even a causal association of lipopolysaccharide in stroke was suggested in this study, which is the first one exploring the genetic background of endotoxemia 117 …”
Section: Discussionmentioning
confidence: 99%
“…Finnish subjects. 117 Altogether, the genome-wide association study found 741 single-nucleotide polymorphisms in five independent loci in chromosomes 3, 4, 5, 11, and 15, which explained up to 9.2% of the lipopolysaccharide activity variation. The loci were associated with expression of genes KNG1 (kininogen-1), F11/KLKB1 (FXI/kallikrein), F12 (FXII), SERPING1 (plasma protease C1 inhibitor), and LIPC (hepatic lipase).…”
Section: Geneticsmentioning
confidence: 96%
See 3 more Smart Citations